COVID-19 Vaccination in Historically Marginalized Communities: Examining Barriers and Facilitators in a Pediatric Population - Marquita C. Genies, MD, MPH; John O. Loftus, BS; Anna C. Sick-Samuels, MD, MPH; Rupali J. Limaye, PHD, MPH, MA; Jessica A. Duchen, MPH; Jeffrey J. Fadrowski, MD (AJPM Focus)
Introduction: COVID-19 hospitalization rates among unvaccinated children are double of that of vaccinated children, and this difference is greater among racial and ethnic minority children. Vaccination rates among children remain suboptimal. Few studies have characterized barriers to COVID-19 vaccination among historically marginalized communities. Methods: From January 2022 to May 2022, parents and guardians of children aged 12 months to 18 years presenting for pediatric care at a hospital-based primary care clinic were surveyed about perceptions of COVID-19 vaccines, intentions to vaccinate their child, and trusted sources of information. Results: A total of 113 parents/guardians participated, with 92% self-identifying with a historically marginalized racial/ethnic group. A total of 54% of respondents either did not plan to vaccinate their child against COVID-19 or were unsure. The obstacles to vaccination most frequently cited were related to (1) unknown side effects, (2) the rapid development of the vaccine, and (3) unsafe ingredients. Worries about being used as experimental subjects and potential impacts on fertility were also reported. Parents who planned to vaccinate their child reported higher rates of trust in doctors, local clinics, hospitals, and health departments. Conclusions: High rates of COVID-19 vaccination hesitancy exist among parents/guardians from historically marginalized groups. Barriers to vaccination were frequently related to side effects, whereas a high level of trust in healthcare providers as sources of information may be a facilitator. Strategies to improve health outcomes and boost vaccination rates should focus on equipping pediatric healthcare providers with the knowledge and skills necessary to address these known barriers to COVID-19 vaccination.